Structure and reactivity of silica-supported titanium and molybdenum(IV) amido complexes. - Beaudoin, Marcel Camille. (University of Ottawa (Canada), 2002)
This thesis is divided into 5 major sections. The first section covers the reactions of Ti(NR2)4 (R is methyl or ethyl) with the surface of partially dehydroxylated silica. This leads to the formation of well-defined grafted titanium complexes. The stoichiometry of the grafting reactions depends upon the degree of dehydroxylation of the silica. When the silica is pretreated at 500°C, ≡SiOTi(NR2)3 is formed, while on silica which has been dehydroxylated at 200°C, (≡SiO) 2Ti(NR2)2 is the product. The second section examines the spontaneous transformations experienced by the bis(dialkylamido)titanium fragments upon standing or exposure to vacuum. beta-H abstraction results in elimination of one equivalent of amine, leaving an eta 2-imine ligand coordinated to titanium. While the N-methylmethanimine complex is stable, the N-ethylethanimine complex undergoes a further loss of ethylene to yield a stable ethylimidotitanium(IV) surface complex. These transformations are catalyzed by the residual surface hydroxyls. The third section describes the reactivity of the bis(dialkylamido)titanium fragments towards amines. Exposure to ammonia induces beta-H abstraction, producing 1 equivalent of dialkylamine and resulting in the formation of eta 2-imine complexes instead of the expected transamination products. The N-ethylethanimine complex, under prolonged vacuum, loses ethylene to produce ethylimidotitanium(IV). Other amines, including dialkylamines and aprotic amines such as pyridine and NEt3, induce the same imine complex formation. The fourth section deals with the reactions of the imine and imido complexes with Ti(NR2)4. Both reactions result in grafting of an additional 2 wt. % Ti onto the silica, in the absence of surface hydroxyls and the formation of one equivalent of the corresponding amine. Dinuclear surface complexes containing bridging imine, imido, or siloxo ligands are proposed as products. The final section involves the characterization of the surface complexes produced upon exposure of partially dehydroxylated silica to Mo(NR2) 4 (R is methyl or ethyl). When R is methyl, grafting on silica pre-treated at 200 or 500°C results in reactions analogous to Ti(NMe2) 4. However, Mo(NEt2)4 displays a reactivity that is significantly different from its Ti analogue. The maximum Mo loading is double that expected for the number of surface hydroxyl groups available. Furthermore, the amount of diethylamine released is 1.5 times higher than expected (treatment of silica at 500°C) or twice as high (silica pre-treatment at 200°C). Spontaneous beta-H abstraction and elimination of diethylamine is proposed to form an N-ethylethanimine complex of molybdenum(IV), which then reacts further with Mo(NEt2)4 to form a dimolybdenum complex with bridging imine ligands.
Keywords: Chemistry, Inorganic.